Предмет: Алгебра,
автор: Afros
Упростите выражение
5а - (8а - 6)
6а - b + (3b - 9a)
12 - 5 (4p - 3)
Буду очень благодарна, заранее спасибо!
Ответы
Автор ответа:
0
1)5а-8а+6=-3а+6=3(2-а)
2)6а-б+3б-9а=-3а+2б=2б-3а
3)12-20р+15=27-20р
2)6а-б+3б-9а=-3а+2б=2б-3а
3)12-20р+15=27-20р
Автор ответа:
0
5a - (8a - 6) = 5a - 8a + 6 = 6 - 3a = 3(2 - a)
6a - b + (3b - 9a) = 6a - b + 3b - 9a = 2b - 3a
12 - 5(4p - 3) = 12 - 20p + 15 = 27 - 20p
6a - b + (3b - 9a) = 6a - b + 3b - 9a = 2b - 3a
12 - 5(4p - 3) = 12 - 20p + 15 = 27 - 20p
Похожие вопросы
Предмет: Английский язык,
автор: panda658
Предмет: Химия,
автор: Biko2024
Предмет: Английский язык,
автор: banu1940
Предмет: География,
автор: Gribochek40
Предмет: Физика,
автор: mudakovich1991